1999
DOI: 10.1038/sj.bjc.6690532
|View full text |Cite
|
Sign up to set email alerts
|

Oral topotecan: bioavailability and effect of food co-administration

Abstract: SummaryThe aims of the study were twofold: (1) to evaluate the effect of food on the relative oral bioavailability of topotecan gelatin capsules in patients with solid tumours, and (2) to determine the absolute bioavailability of oral topotecan with reference to the intravenous (i.v.) formulation. The study had a randomized two-period cross-over design. On day 1 of the first treatment course patients were administered 2.3 mg m -2 day -1 of oral topotecan with or without a high-fat breakfast. They crossed over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 15 publications
2
22
1
Order By: Relevance
“…A clinical study with topotecan gelatin capsules has indeed revealed a moderate bioavailability of 42%. 37 We expect that BCRP expression in the human small intestine and colon will not have a major influence on the bioavailability of BNP1350. Our previous human tumor xenograft studies, predicting a 67% oral bioavailability for BNP1350, support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study with topotecan gelatin capsules has indeed revealed a moderate bioavailability of 42%. 37 We expect that BCRP expression in the human small intestine and colon will not have a major influence on the bioavailability of BNP1350. Our previous human tumor xenograft studies, predicting a 67% oral bioavailability for BNP1350, support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…There has been an increasing clinical interest in developing oral formulations of many cytotoxic agents. Oral topotecan has a 30%-40% bioavailability and no known food or drug interactions [33][34][35]. (For more details, see Gralla [36].)…”
Section: Oral Topotecanmentioning
confidence: 99%
“…Based on these findings, phase I and II studies were undertaken with daily times five oral treatment and low-dose continuous infusion in cancer patients (1, 8 -10). However, topotecan has moderate and variable oral bioavailability of 42 F 13% (10,11). This was unexpected as topotecan is water soluble, forms a chemically stable equilibrium between the lactone and the carboxylate form under physiologic conditions, and lacks significant systemic first-pass metabolism (12).…”
mentioning
confidence: 99%